Allelopathic Effects of Artemisia judaica and A. campestris Aqueous Extracts on Lactuca sativa L Seeds Germination - Abdulhamid Giweli; Alramah Said; Abdulwahab Kammon (African Journal of Advanced Pure and Applied Sciences, 2025)
This study investigated the allelopathic potential of aqueous extracts from two Libyan Artemisia species, Artemisia judaica and Artemisia campestris, on the seed germination and germination rate of Lactuca sativa L. Aerial parts of the plants were collected during the flowering stage in February 2020 from Zintan, Libya. Qualitative phytochemical analysis of the aqueous extracts revealed the presence of tannins, flavonoids, and saponins in both species, while phlobatannins and terpenoids were absent. A bioassay demonstrated that both A. judaica and A. campestris extracts exhibited significant allelopathic activity, inhibiting Lactuca sativa seed germination and decrease the germination rate (GR) in a dose-dependent manner. Complete inhibition of germination (100% IP) was observed at concentrations of 10 mg/ml and 20 mg/ml for both species. The findings suggest that the observed allelopathic effects are likely due to the identified phytochemical constituents, and that these Artemisia species could serve as promising sources for natural herbicides in agricultural weed control.